Implementasi Peraturan Menteri Sosial Nomor 10 Tahun 2017 Dalam Pelaksanaan Program Keluarga Harapan Di Desa Sidomulyo Kecamatan Bilah Hilir Kabupaten Labuhanbatu - Nur’aidah Azzahra (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2022)
This study aims to determine the implementation of the Minister of Social Affairs Regulation Number 10 of 2017 in the Implementation of the Family Hope Program in Sidomulyo Village, Bilah Hilir District, Labuhanbatu Regency. The type of research conducted is descriptive research with a qualitative approach. Based on the results of the study, it is known that the implementation of the Minister of Social Affairs Regulation Number 10 of 2017 in the Implementation of the Family Hope Program in Sidomulyo Village, Bilah Hilir District, Labuhanbatu Regency has been implemented, but there are several obstacles. target, Human resources in the implementation of the Family Hope Program in Sidomulyo Village are less competent, so many people should be entitled to benefits in the Family Hope Program, but in the field there are still many who have not benefited from PKH, the bureaucratic structure is in accordance with standard operating procedures ( SOP), the disposition in the implementation of the family of hope program in Sidomulyo Village has been carried out well, but there are obstacles, namely the lack of awareness of the beneficiary families in carrying out their obligations as beneficiary families of the program. Hope Family